Organic Aerosol Particle Chemical Properties Associated With Residential Burning and Fog in Wintertime San Joaquin Valley (Fresno) and With Vehicle and Firework Emissions in Summertime South Coast Air Basin (Fontana). Issue 18 (20th September 2018) - Chen, Chia‐Li; Chen, Sijie; Russell, Lynn M.; Liu, Jun; Price, Derek J.; Betha, Raghu; Sanchez, Kevin J.; Lee, Alex K. Y.; Williams, Leah; Collier, Sonya C.; Zhang, Qi; Kumar, Anikender; et al.
Abstract: Organic aerosol mass (OM) components were investigated at Fresno in winter and at Fontana in summer by positive matrix factorization of high‐resolution time‐of‐flight aerosol mass spectra and of Fourier Transform infrared spectra, as well as by k ‐means clustering of light‐scattering (LS) aerosol single‐particle spectra. The results were comparable for all three methods at both sites, showing different contributions of primary and secondary organic aerosol sources to PM1 . At Fresno biomass burning organic aerosol contributed 27% of OM on low‐fog days, and nitrate‐related oxidized OA (NOOA) accounted for 47% of OM on high‐fog days, whereas at Fontana very oxygenated organic aerosol (VOOA) components contributed 58–69% of OM. Amine and organosulfate fragment concentrations were between 2 and 3 times higher on high‐fog days than on low‐fog days at Fresno, indicating increased formation from fog‐related processes. NOOA and biomass burning organic aerosol components were largely on different particles than the VOOA components in Fresno, but in Fontana both NOOA and VOOA components were distributed on most particle types, consistent with a longer time for and a larger contribution from gas‐phase photochemical secondary organic aerosol formation in summer Fontana than winter Fresno. Uncommon trace organic fragments, elevated inorganic, and alcohol group submicron mass concentrations persisted at Fontana for more than 5 days after 4 July fireworks. These unique aerosol chemical compositions at Fresno and Fontana show substantial and extended air‐quality impacts from residential burning and fireworks. Key Points: Oxidized organic and amine fragment concentrations were higher on high‐fog days than on low‐fog days at Fresno Uncommon trace organic fragments ( m/z 27 and m/z 63), nitrate, sulfate, and single‐particle types associated with fireworks persisted at high concentrations at Fontana for 5 days after emission Nitrate‐related and other organic aerosol mass factors were largely on different particle types at Fresno but were mixed at Fontana